A Critical Reading of the Legal Regulation of Violence against Women in Lamu, Kenia, from the Contribution of Indigenous Women - Fernández Quiroga, Ana (FEMERIS: Revista Multidisciplinar de Estudios de Género, 2019)
The Gender Violence is a global problem of the first order. Their manifestations are very diverse and should be treated as an inter-sectorial problem, since ethnic, class or socio-cultural differences influence their different degrees of oppression. There are innumerable legal instruments that have been promulgated for their eradication but without greatly improving the figures. Partly because it has been forgotten on many occasions to have the voices and experiences of women who have suffered these experiences and has fallen into false paternalism in its regulation and elsewhere because some of its manifestations are carried out in private spaces and remain invisible, especially sexual assaults within marriage. This communication refers to an investigation carried out in an island of Kenya called Lamu where different projects of social and economic empowerment of indigenous women are developed. It deals with knowing the degree of knowledge and legitimacy of the legislation against sexist violence, the barriers in the judicial process and the existing diversity according to ethnicity, religion or socio-cultural level, as well as resilience strategies of the women themselves in the face of these violence. It is carried out from a qualitative methodological framework where the key piece is the in-depth interviews with indigenous women themselves. From it we will draw, among other conclusions, that when the judicial process of divorce and that of sexual violence are independent, in the absence of economic capacity, the second is abandoned.